2009
DOI: 10.1089/thy.2008.0407
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence After Treatment of Micropapillary Thyroid Cancer

Abstract: Patients with micropapillary multifocal disease have a reduced risk of recurrence after a T/NTT compared with less surgery. A randomized, controlled trial is necessary and feasible to determine if radioiodine ablation of thyroid remnants is advantageous in patients with intrathyroidal micropapillary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 18 publications
12
104
3
4
Order By: Relevance
“…Retrospectively analyzing 889 patients with pT1-2 well-differentiated thyroid cancer, Nixon and colleagues 30 found that patients undergoing thyroid lobectomy had no difference in local or regional recurrence. In contrast, Ross and colleagues 31 showed that in 611 patients, micropapillary multifocal disease, in particular, demonstrated reduced risk of recurrence after total thyroidectomy (6%) compared with patients who underwent less than complete resection (18%). Given that the majority of our fvPTC cohort demonstrated multifocal disease, patients who undergo lobectomy alone might benefit from ongoing monitoring of the contralateral side, with the understanding that the likelihood of a clinically significant cancer developing is low.…”
Section: Discussionmentioning
confidence: 92%
“…Retrospectively analyzing 889 patients with pT1-2 well-differentiated thyroid cancer, Nixon and colleagues 30 found that patients undergoing thyroid lobectomy had no difference in local or regional recurrence. In contrast, Ross and colleagues 31 showed that in 611 patients, micropapillary multifocal disease, in particular, demonstrated reduced risk of recurrence after total thyroidectomy (6%) compared with patients who underwent less than complete resection (18%). Given that the majority of our fvPTC cohort demonstrated multifocal disease, patients who undergo lobectomy alone might benefit from ongoing monitoring of the contralateral side, with the understanding that the likelihood of a clinically significant cancer developing is low.…”
Section: Discussionmentioning
confidence: 92%
“…Adicionalmente, y aunque el número de casos es pequeño, encontramos igual cantidad de pacientes con recidiva tratados y no tratados con radioyodo; algo similar a lo encontrado por Ross et al 22 , quien demostró que la terapia con I-131 no redujo las recurrencias en pacientes con patología multifocal o con linfonodos afectados; esto debiera ser estudiado por ensayos clínicos controlados y aleatorizados, a fin de establecer el verdadero valor de la terapia con radioyodo en este tipo de pacientes.…”
Section: Discussionunclassified
“…The data collection and analytical methods of the NTCTCS have been described elsewhere (8,9,(14)(15)(16)(17)(18)(19)(20). Briefly, 11 North American centers contributed patient data, with registration beginning in January 1987 (this data analysis captures patients registered through to 2011).…”
Section: Registry Protocol and Data Collectionmentioning
confidence: 99%